Civil Defence in South Africa - Martienssen, Rex D; Hanson, Norman L; WGM (The Cape, Natal, Orange Free State and Transvaal Provincial Institutes of South African Architects and the Chapter of South African Quantity Surveyors, 1940)
"The architect's training in large scale planning, in the co-ordination of the many and varied technical activities connected with building and in the adjustment of related and sometimes conflicting programme requirements, gives him a special place in the formulation and carrying out of comprehensive measures for Air Raid Protection."
Keywords: South Africa Civil Defence; Air Raid Protection